2020
DOI: 10.1177/2192568220906173
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Cervical Disorder—Stand-alone Cage Versus Cage and Cervical Plate: A Systematic Review

Abstract: Study Design: Systematic review. Objectives: The objective of this study was to compare clinical and radiological outcomes following discectomy and anterior cervical fusion for the treatment of cervical degenerative disorder performed with stand-alone cages and anterior cervical plates. Methods: Electronic searches were performed in the MEDLINE, LILACS, and Cochrane Systematic Reviews databases, according to PRISMA guidelines, with no language or date restriction. The review was registered in PROSPERO under nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Similarly, a recent meta-analysis by Gabr et al demonstrated that stand-alone anchored spacers were associated with less dysphagia compared to the plate-screw construct [ 16 ]. Lastly, a systematic review by Boer et al showed that there was no difference in clinical (visual analog scale, neck disability index) or radiological (cervical lordosis and fusion) outcomes between the two groups, but stand-alone devices were associated with shorter operative time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent meta-analysis by Gabr et al demonstrated that stand-alone anchored spacers were associated with less dysphagia compared to the plate-screw construct [ 16 ]. Lastly, a systematic review by Boer et al showed that there was no difference in clinical (visual analog scale, neck disability index) or radiological (cervical lordosis and fusion) outcomes between the two groups, but stand-alone devices were associated with shorter operative time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, an LSC could provide immediate load-bearing support to the anterior column of the cervical spine and may enhance the rate of arthrodesis. Previous studies reported that LSC provided comparable stability and reduced the damage to soft tissues and plate-related complications with a satisfactory clinical outcome (7)(8)(9)(10)(11)(12). Nevertheless, previously published studies showed that there were no advantages of LSC in clinical and/or radiologic outcomes and/or complications compared with APC (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…During almost 60 years of anterior access cervical discopathy, this method underwent many modifications. It became minimal invasive, instead of using initially taken blocks taken from the iliac bone, cage made of artificial substitutes such as titanium, PEEK was used [5,6]. Dynamic implants called artificial discs are also used, which maintain the mobility of the operated segment.…”
Section: Introductionmentioning
confidence: 99%